(untitled) (American Journal of Islam and Society, 1997)
Ever since the Qur’an was revealed, Muslims have been making great efforts to understand and live in accordance with it. Within a very short period of time after the Prophet’s death, schools of fish emerged in the Hijaz, Iraq, and Syria. They defined the sources of the religion (al-din) and engaged in developing methods to better understand them. By the early part of the second century, more systematic approaches appeared; the roots of the schools that emerged reached back to the Companions of the Prophet as well as to the Prophet himself.’ Their approaches represented man’s natural tendencies to understanding the din. Many schools appeared only to fade away and be replaced by ones more comprehensive in their approach. In the late second century, Imam al-Shafi’i (150- 204 A.H.) put forward the first systematic methodology of fiqh. In his work, al-Risalah, Imam al-Shafi’i offered a methodoIogy for the very purpose of understanding the din. Of course, the methodology took for granted a certain definition of Islam. Even though his methodology drew from prior lines of thought, it is widely accepted that as an original methodology, the Imam’s theory of fiqh drastically transformed the perception of Islam that had hitherto prevailed." In order to change the approach toward the din, he redefined concepts such as Sunnah and ijtihad. He identified ijtihad with qiyas; and whereas the term Sunnah had been used for the practice of the Muslim community, the Imam restricted its application to the Sunnah of the Prophet and the companions. In his vocabulary the concept of hikmah took on considerable importance. Al-Shafi’i can almost be singled out by his definition of the concept of hikmah from other Muslim scholars. In order to establish and consolidate the authority of the Sunnah on the basis of the Qur’an, he interpreted and defined this Qur’anic concept as being synonymous with the Sunnah ...